Assessment of Predictive Biomarkers of the Response to Pazopanib Based on an Integrative Analysis of High-grade Soft-tissue Sarcomas: Analysis of a Tumor Sample from a Responder and Patients with Other Soft-tissue Sarcomas. Issue 11 (November 2020) - Suehara, Yoshiyuki; Kohsaka, Shinji; Yamaguchi, Shigeo; Hayashi, Takuo; Kurihara, Taisei; Sano, Kei; Sasa, Keita; Akaike, Keisuke; Ueno, Toshihide; Kojima, Shinya; Ikegami, Masachika; Mizuno, Sho; et al.
Abstract: Background: Soft-tissue sarcomas are a rare group of malignant tumors that usually are treated with surgical excision and radiation therapy, but recently, pazopanib, an oral tyrosine kinase inhibitor, has been used in patients with metastases who do not respond to standard chemotherapy regimens. Based on patients with advanced soft-tissue sarcomas who had received prior chemotherapy, several clinical studies have reported the survival and sensitivity (approximately 5% to 10% sensitive) of patients with soft-tissue sarcomas treated with pazopanib. Recently, next-generation sequencing (NGS) technologies have been used to provide a wide genetic information and to develop personalized medicine in cancer treatment. However, there are few reports and no genetic analyses of patients with soft-tissue sarcomas who had a complete response (CR) to pazopanib. Questions/purposes: We described the clinicopathologic features of a patient with a rare, advanced soft-tissue sarcoma who achieved a CR to pazopanib treatment. Furthermore, integrative analyses using NGS and arrays were performed to elucidate characteristic alterations, including gene mutations, copy number changes, and protein expression that were associated with response to pazopanib. Additionally, functional analyses consisting of in vitro and in vivo assays were also performed to elucidate whether the identified alterations were associated with oncogenic abilities and drug responses. Methods: In a sample from a 70-year-old woman with an advanced soft-tissue sarcoma treated for 1 month with 800 mg of oral pazopanib daily, CT scans demonstrated a CR to treatment. To our knowledge, there have been no patients with soft-tissue sarcomas among several clinical trials of pazopanib that have achieved a CR and therefore, our patient is considered to be extremely rare. We performed an integrative analysis including whole-exome sequencing, transcriptome sequencing, and phosphorylation profiling of receptor tyrosine kinases (RTK) using tumor samples from a patient with a CR matched to normal samples. From here on we will refer to this patient as having a CR, although a short term high-grade partial response may be more accurate. These analyses were performed using NGS and the phosphoreceptor tyrosine kinase (phospho-RTK) array. As a validation study, we also performed target sequencing using three samples from patients with long-term stable disease and two samples from patients with progressive disease who responded to pazopanib treatment. In addition, characteristic gene alterations that were identified according to the response to pazopanib in one patient with a CR, in three patients with long-term stable disease, and in 27 patients with high-grade soft-tissue sarcomas with different histologic subtypes and different responses to pazopanib were verified by quantitative real-time polymerase chain reaction. We conducted a focus formation assay to evaluate the transforming activities of these genomic alterations. Results: In the patient with a CR to pazopanib, we identified several somatic mutations including Fms related receptor tyrosine kinase 1 ( FLT1 ) p.G38S, platelet-derived growth factor receptor alpha ( PDGFRA ) p.T83S, and platelet-derived growth factor receptor beta ( PDGFRB ) exon 13 skipping. Amplification at chromosome 12q13-14 encompassing GLI family zinc finger 1 ( GLI1 ) and cyclin-dependent kinase-4 ( CDK4 ) was also detected. Furthermore, an elevated PDGFRB phosphorylation level was observed in the tumor. In target sequencing analyses in five patients, one of three patients with long-term stable disease had 12q13-14 amplification. The mRNA expression of GLI1, CDK4, and pazopanib targets including PDGFRA, PDGFRB, vascular endothelial growth factor receptor (VEGFR)1-3, and stem cell factor receptor ( KIT ) in samples from the patient with a CR, and 27 patients with high-grade soft-tissue sarcomas was verified. The expression of GLI1 was characteristically increased in the patient with a CR and in those with long-term stable disease relative to other patients with soft-tissue sarcomas. Overexpression of GLI1 showed strong transforming potential in 3T3 cells. Moreover, the overexpression of GLI1 upregulated the expression of the PDGFRB protein and promoted phosphorylation, which was dose-dependently inhibited by pazopanib. However, inhibition of GLI1-induced transformation by pazopanib was limited in the focus formation assay; therefore, mechanisms other than PDGFRB activation may contribute to transformation. Conclusions: We identified several gene alterations that might be associated with a CR and long-term stable disease in patients who received pazopanib for advanced soft-tissue sarcomas. We therefore believe that this distinct molecular profile warrants further investigation to identify predictive biomarkers of the response to pazopanib. Clinical Relevance: Our findings identify molecular mechanisms that possibly explain the high sensitivity of soft-tissue sarcomas to pazopanib and may lead to the development of predictive biomarkers and novel therapies in patients with this and other types of soft-tissue sarcomas.